The impact of facial emotional expression on the effectiveness of charitable advertisements: the role of sympathy and manipulative intent. (19th March 2022) - Kang, In‐Hye; Leliveld, Marijke C.; Ferraro, Rosellina
Abstract: In charitable advertisements, organizations often display the image of a person in need with different facial emotional expressions. Prior research showed the positive effect of using a sad‐ (vs. happy‐ or neutral‐) faced image in evoking sympathy from viewers. Across five studies ( N = 2141), we demonstrate that a sad‐faced image evokes not only sympathy but also an inference about the organization's manipulative intent. Moreover, we show that inference of manipulative intent and sympathy simultaneously mediate the effects of facial expression on donation and on attitude toward the advertising campaign, but in opposing directions. While greater sympathy leads to larger donation, greater inference of manipulative intent lowers donation, together contributing to a null effect of facial expression on donation. In contrast, using a sad‐faced image reduces attitude toward the advertising campaign because the mediating effect of inference of manipulative intent tends to be larger than the mediating effect of sympathy in absolute size. The negative effect of a sad‐faced image on attitude toward the advertising campaign is attenuated when the prominence of the image is low (vs. high). Finally, we show that these effects also emerge in the cause‐related marketing advertising context.